Digital maturity as a determinant of business resilience in microenterprises in Ibero-America: a post COVID-19 analysis (2023)
This paper examines the relationship between the level of digital maturity and business resilience in microenterprises in Ibero- America immediately after Coronavirus 2019 (COVID-19). The results of 7265 surveys of microbusinesses in 18 countries were analyzed. It was found that businesses with a higher level of digital maturity presented a higher level of resilience understood as an improvement in their sales after facing a crisis such as the pandemic.